PENGARUH BEBAN KERJA TERHADAP STRESS KERJA PERAWAT IGD RSUD. A. WAHAB SJAHRANIE - ., Bibit Nurcahyawati (MOTIVASI, 2016)
AbstractThis study aims to determine whether there is a positive and significant influence between the workload of the working stress on hospital emergency room nurse. A. Wahab Sjahranie. The hypothesis proposed in this study is that there is a positive and significant influence between workload against work stress. Subjects in this study were hospital emergency room nurse. A. Wahab Sjahranie totaling 50 subjects. The scale used in this study is the job stress scale refers to those aspects of psychological, physiological and behavioral proposed by Handoko and the scale of the workload with aspects such as mental workload and physical workload. The results showed there was a positive influence between workload against work stress, which in point of product moment correlation analysis is r = 0.458 (p <0.05), which means that the variable job stress and workload has a high correlation. If the stress of work and the workload are correlated, then the chances of factors can affect between them with a chance 0% (p = 0.000). The hypothesis of this study is stated in the receipt.